A descriptive analysis of disagreement strategies: the case of Iranian EFL learners - Farashaiyan, Atieh; Muthusamy, Paramasivam (Macrothink Institute, 2016)
The purpose of this research was to describe the L2 pragmatic knowledge of Iranian EFL learners by producing the speech act of disagreement in English in different situations. One hundred and twenty Iranian EFL learners took part in this study. The required data were accumulated through a Written Discourse Completion Task (WDCT). The results showed that most participants tended to make use of more indirect strategies (44.85%) to disagree with another speaker’s statement either with higher or lower power or within different social distance. The respondents’ most frequent strategy use refers to counterclaims with 44.8%. On the other hand, challenges with 8.8% and Irrelevancy of claims with 3.2% were respectively among the least frequent strategies used in all situations. The results showed that learners almost utilized the same strategies in different disagreement situations with the same frequency. Therefore, it indicates that they did not notice the situational variables of social power, distance and imposition to vary their choice of strategy. In other words, they did not have the contextual understanding of the mentioned factors. Therefore, the results can suggest that the learners lack sufficient pragmatic knowledge in performing the studied speech act. The implication of this study is for Iranian language instructors, materials writers and curriculum developers.